Lean Accounting and Lean Entrepreneurship (American Journal of Social Development and Entrepreneurship, 2023)
This study examined the relationship between lean accounting and lean entrepreneurship in Nigeria. The study adopted a quasi-experimental design and cross-sectional design. Data were generated by quantitative and qualitative method. The employed used purposive sampling techniques and non-proportionate stratified random sampling techniques. A total population of 400, a sample size estimate of 200 was determined using Krejcie and Morgan Table. Also, 200 copies of the questionnaire were distributed to the accessible entrepreneurs’, while 189 copies were completed and retrieved. The instruments were validated with a reliability above 0.7 Co-efficient, using Parallel Method to determine the reliability. Two research questions and two hypotheses were raised which were tested with regression analysis and KMO/Barllet’s test for the sampling adequacy for data appropriateness and sphericity respectively via SPSS 25 version. From the findings, the concept of lean accounting positively impacts business creation. In conclusion, lean improvement and lean thinking have a significant influence on the business creation of firms. Based on the findings and conclusion, this study contributes to the knowledge that business creation could be achieved by practicing lean entrepreneurship on value creation, value capture and wealth creation. It could be recommended that lean improvement and lean thinking should be practiced without compromise and bias. The top management of enterprise should engage services of professionals in lean entrepreneurship to train staff and intrapreneurs on business creation. Business creation should be paramount mindset of the stakeholders of organizations.